Indonesian Curriculum Reform in Policy and Local Wisdom: Perspectives from Science Education (Jurnal Pendidikan IPA Indonesia, 2021)
This article summarizes the issue of Indonesian curriculum reform in policy and local wisdom. The perspectives on science education influence the analysis and discussions. This paper is part of a position paper (PP) in which the writers tailored their ideas based on their experiences and literature review. The views regarding curriculum policy, science local wisdom, and ethnoscience were developed based on theoretical and empirical literature regarding these issues. The discussion is divided into five parts: curriculum policy and policy borrowing, philosophy of Indonesian local wisdom, cultural-based learning, science local wisdom and ethnoscience, and policy borrowing versus local wisdom. The significance of the results gives a view to the government, academicians, policymakers, and educational communities.